Fano effect of a parallel-coupled triple Rashba quantum dot system - 贺泽龙 吕天全 崔莲 薛惠杰 李林军 尹海涛 (Chinese physics B, 2011)
Using the nonequilibrium Keldysh Green＇s function technique, the Fano effect of a parallel-coupled triple Rashba quantum dot system is investigated. The conductance as a function of electron energy is numerically calculated. Compared with the case of a parallel-coupled double quantum dot system, two additional Fano resonance peaks occur in the conductance spectrum. By adjusting the structural parameters, the two Fano resonance peaks may change into the resoaance peaks. In addition, the influence of Rashba spin-orbit interaction on the conductance is studied.